Jenifer Williams at the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows an African American women, Jenifer Williams, at the 1986 y-Walk. She is standing at a microphone and possibly has papers or binders in her arms. There is sound equipment sitting on a chair in front of her and the landscaping for the YWCA building is behind her.